Static and dynamic stretching have same effects on lower extremity joints kinematics and muscular EMG variability in healthy active males during pedaling - Ali Abbası; Heydar Sadeghı; Mehdi Zamanıan (Türk Spor ve Egzersiz Dergisi)
Previous studies about the effect of static and dynamic stretching on forthcoming performance have been reported different results. The purpose of present study was to examine the effects of acute static and dynamic stretching on kinematics and EMG variability of lower extremity joints and Muscles in healthy active males during pedaling. Fifteen physically-active male students voluntarily participated in this research. Lower extremity kinematics and EMG data from six lower extremity muscles were collected during 30 pedaling cycle at 70 RPM in situation where there is no stretching (baseline) and after 2, 5, and 10 min post static and dynamic stretching by MIE motion analysis system. Filtered EMG signals and hip, knee and ankle joints angle and angular velocity were extracted for constructing time series and variability calculation. The results of repeated measures ANOVA showed that there are no significant difference in the variability of Muscular EMG and joints angle and angular velocity at 2, 5, and 10 minutes after static and dynamic stretching (P gt; 0.05). Contrary to previous studies that encouraged coaches and athletes to not use static stretching or to use dynamic stretching instead, the results suggest cyclists can benefits from both stretching types in warm-up programs.